Analysis of the adiponectin paradox in healthy older people. Issue 1 (18th November 2022) - Walowski, Carina O.; Herpich, Catrin; Enderle, Janna; Braun, Wiebke; Both, Marcus; Hasler, Mario; Müller, Manfred J.; Norman, Kristina; Bosy‐Westphal, Anja
Abstract: Background: It remains unknown why adiponectin levels are associated with poor physical functioning, skeletal muscle mass and increased mortality in older populations. Methods: In 190 healthy adults (59–86 years, BMI 17–37 kg/m 2, 56.8% female), whole body skeletal muscle mass (normalized by height, SMI, kg/m 2 ), muscle and liver fat were determined by magnetic resonance imaging. Bone mineral content (BMC) and density (BMD) were assessed by dual X‐ray absorptiometry ( n  = 135). Levels of insulin‐like growth factor 1 (IGF‐1), insulin, inflammation markers, leptin and fibroblast growth factor 21 were measured as potential determinants of the relationship between adiponectin and body composition. Results: Higher adiponectin levels were associated with a lower SMI ( r  = −0.23, P  < 0.01), BMC ( r  = −0.17, P  < 0.05) and liver fat ( r  = −0.20, P  < 0.05) in the total population and with higher muscle fat in women ( r  = 0.27, P  < 0.01). By contrast, IGF‐1 showed positive correlations with SMI ( r  = 0.33), BMD ( r  = 0.37) and BMC ( r  = 0.33) (all P  < 0.01) and a negative correlation with muscle fat ( r  = −0.17, P  < 0.05). IGF‐1 was negatively associated with age ( r  = −0.21, P  < 0.01) and with adiponectin ( r  = −0.15, P  < 0.05). Stepwise regression analyses revealed that IGF‐1, insulin and leptin explained 18% of the variance in SMI, and IGF‐1, leptin and age explained 16% of the variance in BMC, whereas adiponectin did not contribute to these models. Conclusions: Associations between higher adiponectin levels and lower muscle or bone mass in healthy older adults may be explained by a decrease in IGF‐1 with increasing adiponectin levels.